EFEKTIVITAS PEMBELAJARAN BERBASIS HOTS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SEKOLAH DASAR - Ricky Gustiawan; Desyandri (STKIP Subang, 2022)
This research is motivated by the activities and learning outcomes of HOTS fifth grade students at SDN 15 Kapalokoto Kec. Sungaipua is still low. It can be seen that many students are less enthusiastic in learning. This research was conducted on class students of SDN 15 Kapalokoto Kec. Sungaipua Academic Year 2022/2023. This study aims to determine the effectiveness of HOTS-based learning using the problem-based learning model for elementary school students. The design or experimental research design used is the Randomized Control Group Only design with the research method using quasi-experimental. The research subjects were fifth grade students at SDN 15 Kapalokoto Kec. Sungaipua with a total of 40 people. The results showed that the effectiveness of HOTS-based learning using the PBL model increased more compared to conventional learning. Thus it can be concluded that the results of HOTS-based learning in class V students at SDN 15 Kapalokoto Kec. Sungaipua, can increase effectively, by using the Problem Based Learning (PBL) model. Keywords: Problem Based Learning Model, HOTS, Elementary Schools